Developing a FlipHTML5-Based Digital Module Integrating Local Wisdom for Teaching Descriptive Texts in Junior High School - Sri Puji Astuti; Syarifuddin Syarifuddin; Machdalena Vianty (AL-ISHLAH: Jurnal Pendidikan, 2026)
Descriptive-text instruction in junior high schools often relies on generic materials that lack cultural relevance and digital interactivity. This study addresses that gap by developing local-wisdom-based teaching materials for descriptive-text learning, delivered through the FlipHTML5 digital platform. The research aims to produce materials that are valid, practical, and effective in supporting English as a Foreign Language (EFL) learning. Using a Research and Development (RD) approach with the ADDIE model (analysis, design, development, implementation, evaluation), the study first conducted a needs analysis with 220 students to identify instructional challenges. Product trials were then carried out with 30 students, involving one-to-one testing, small-group trials (10 students), and field trials (20 students). Instruments included expert validation rubrics (content, language, media), practicality questionnaires (teachers and students), and pre-/post-tests of descriptive-text writing. Data were analyzed using descriptive statistics and the N-gain formula to measure learning improvement. Results indicate that the developed materials achieved a very valid category with an average expert score of 94.96%, were rated practical by teachers and students (80%), and demonstrated high effectiveness with an N-gain score of 0.79, reflecting significant improvement in students’ writing skills. This research contributes to the field by providing culturally responsive EFL materials enriched with local wisdom and supported by empirical evidence of validity, practicality, and effectiveness. It also highlights the potential of digital flipbooks as innovative instructional media for junior high school contexts.